Peristaltic Transport of a Viscoelastic Fluid with Fractional Maxwell Model in an Inclined Channel - Ibrahim .A.H., Ali; M. Abdulhadi, Ahmed (Iraqi Journal of Science, 2023)
This paper is devoted to the study of the peristaltic transport of viscoelastic non-Newtonian fluids with fractional Maxwell model in an inclined channel. Approximate analytical solutions have been constructed using Adomain decomposition method under the assumption of long wave boundary layer type approximation and low Reynolds number. The effect of each of relaxation time, fractional parameters, Reynolds number, Froude number, inclination of channel and amplitude on the pressure difference, friction force and stream function along one wavelength are received and analyzed.